PRICE STABILITY AND SHALLOT MARKET INTEGRATION IN CENTRAL JAVA - Muhammad Luthfie Fadhilah; Anna Fariyanti; Ratna Winardi Asmarantaka (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
The COVID-19 virus is causing economic shocks. If there is no balance of demand and supply, the impact will result in price instability and price integration. Shallot (Allium ascalonicum) is an essential commodity in Indonesia that will impact inflation. Central Java is the largest national producer, and the impact that will be caused will be huge for the national shallot trade. Price fluctuations and integration in Central Java will have an impact due to many farmers and marketing actors involved in the shallot trade. The study aimed to analyze the stability of shallot in Central Java and analyze vertical and horizontal market integration. The methods used are The Coefficient of Variation and VAR/VECM. The results of research on producer prices and consumer prices in the time before and during pandemics are classified as high volume. Although producer prices have decreased volatility (19.73 to 18.43), consumer prices have increased (19.64 to 21.12). On vertical integration, in the long run, only the price of producers with retail traders and large swords with retail traders experience integration. While in the short term, there is only a producer-price relationship affecting the price of retail traders in Central Java which is harmful. The horizontal integration between Jakarta Karamatjati Market, Bandung Kosambi Market, Johar Semarang Market, and Bringharjo Market Yogyakarta experienced long and short-term integration. Johar Semarang Market is influenced by all three markets and only affects Yogyakarta Beringharjo Market.